Penguatan Pemberdayaan Masyarakat Berbasis Sociopreneurship Melalui Potensi Lokal Menjadi Produk Inovasi Unggulan Menuju SDGs - Hasanuddin hasanuddin; Eduart Wolok; Sunardi Sunardi; Idham Halid Lahay; Syarifuddin Achmad; Monica pratiwi; Esta Larosa; Sugeng Pramudibyo; Sri Ayu Ashari; Wahyu Saputra (Universitas Negeri Gorontalo, 2023)
The purpose of implementing this community service is to strengthen community empowerment based on sociopreneurship through local potential to become superior innovation products towards SDGs. The location of the service was carried out in Salinggoha Village which is located in Walea Besar District, Tojo Una-una Regency, Central Sulawesi Province. The method used is based on sociopreneurship, which is a business whose concept originates from social issues in the community through: (1) increasing awareness/attitude, insight/knowledge and community skills, (2) creating superior products and village innovation products that can help the community's economy, and (3) empowerment regarding the importance of forming MSME groups in advancing the village economy. The results of this community service activity are 1) Main Product of Coconut Oil Village, Salinggoha Village Originality, 2) Featured Product of Shredded Fish Typical of Salinggoha, and 3) Product Innovation of Crispy Banana Blossom Chips. It is our hope that in the future the knowledge that we provide to the community can be well received and applied by the community so that later it can bring Salinggoha Village to a better direction.